2014
DOI: 10.1001/jamaophthalmol.2013.5692
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Vitreous Prostaglandin E2Levels After Topical Administration of Ketorolac 0.45%

Abstract: IMPORTANCE Inhibition of proinflammatory prostaglandins in the retina may have therapeutic effects for retinal disease. OBJECTIVE To determine vitreous levels of ketorolac and prostaglandin E 2 (PGE 2 ) in eyes treated with topical ketorolac tromethamine 0.45% (Acuvail). DESIGN, SETTING, AND PARTICIPANTSA prospective comparative interventional study, performed in a university academic hospital, included 24 eyes in 22 consecutive patients undergoing pars plana vitrectomy. INTERVENTION Application of topical ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…Additionally, ketorolac 0.45% use significantly decreased vitreous PGE2 levels in the human eye (Schoenberger et al. ). They also demonstrated that vitreous levels of ketorolac were significantly higher in pseudophakic eyes than in phakic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ketorolac 0.45% use significantly decreased vitreous PGE2 levels in the human eye (Schoenberger et al. ). They also demonstrated that vitreous levels of ketorolac were significantly higher in pseudophakic eyes than in phakic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Ketorolac tromethamine, 0.45%, is preservative free 8 and achieves 2.5-fold higher vitreous levels than older formulations. 25 Its excellent safety, enhanced bioavailability, and lack of preservatives make it well suited for long-term application. It is possible that IL-8 and PDGF-AA contribute to the pathogenesis of DR. Interleukin 8 is a potent chemoattractant and activator of neutrophils 26 and one of the most consistently reported cytokines to have elevated levels in the plasma and vitreous of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although anti‐VEGF is the first line of therapy against CNV in AMD, controlling these particular inflammatory cascades has recently been clinically investigated in an effort to synergistically enhance AMD treatment . Furthermore, association therapy with anti‐VEGF is supported by recent findings of a significant vitreous penetration by NSAIDs, reaching therapeutic concentrations that allow for a significant PGE2 and IL‐8 vitreous reduction . Our group showed that mean vitreous concentrations following topical NSAID administration were as follows: indomethacin 358.6 ± 83.2 pg/mL and 615.6 ± 267 pg/mL, bromfenac 234.3 ± 47.2 pg/mL and 355.6 ± 81.4 pg/mL, and nepafenac 183.8 ± 35.8 pg/mL and 385.0 ± 103.9 pg/mL, respectively for phakic and pseudophakic eyes …”
Section: Discussionmentioning
confidence: 53%